Does growing atmospheric CO2 explain increasing carbon sink in a boreal coniferous forest?. (22nd February 2022) - Launiainen, Samuli; Katul, Gabriel G.; Leppä, Kersti; Kolari, Pasi; Aslan, Toprak; Grönholm, Tiia; Korhonen, Lauri; Mammarella, Ivan; Vesala, Timo
Abstract: The terrestrial net ecosystem productivity (NEP) has increased during the past three decades, but the mechanisms responsible are still unclear. We analyzed 17 years (2001–2017) of eddy‐covariance measurements of NEP, evapotranspiration (ET) and light and water use efficiency from a boreal coniferous forest in Southern Finland for trends and inter‐annual variability (IAV). The forest was a mean annual carbon sink (252 [ ± 42] gC m ‐ 2 a ‐ 1 ), and NEP increased at rate +6.4–7.0 gC m ‐ 2 a ‐ 1 (or ca. +2.5% a ‐ 1 ) during the period. This was attributed to the increasing gross‐primary productivity GPP and occurred without detectable change in ET. The start of annual carbon uptake period was advanced by 0.7 d a ‐ 1, and increase in GPP and NEP outside the main growing season contributed ca. one‐third and one‐fourth of the annual trend, respectively. Meteorological factors were responsible for the IAV of fluxes but did not explain the long‐term trends. The growing season GPP trend was strongest in ample light during the peak growing season. Using a multi‐layer ecosystem model, we showed that direct CO 2 fertilization effect diminishes when moving from leaf to ecosystem, and only 30–40% of the observed ecosystem GPP increase could be attributed to CO 2 . The increasing trend in leaf‐area index (LAI), stimulated by forest thinning in 2002, was the main driver of the enhanced GPP and NEP of the mid‐rotation managed forest. It also compensated for the decrease of mean leaf stomatal conductance with increasing CO 2 and LAI, explaining the apparent proportionality between observed GPP and CO 2 trends. The results emphasize that attributing trends to their physical and physiological drivers is challenged by strong IAV, and uncertainty of LAI and species composition changes due to the dynamic flux footprint. The results enlighten the underlying mechanisms responsible for the increasing terrestrial carbon uptake in the boreal zone. Abstract : Trends and inter‐annual variability of carbon and water exchange of a boreal coniferous‐dominated forest in southern Finland was studied by combining 17 years eddy‐covariance data with process‐model scenarios. We found increase of net carbon sink (+6.4–7.0 gC m −2 a −1 ) but no change in evapotranspiration. The increasing gross‐primary productivity was mostly attributed to management‐stimulated leaf‐area increase, not atmospheric CO2 fertilization. Meteorological conditions created strong inter‐annual variability but did not contribute to decadal trends.